2017
DOI: 10.1098/rspb.2016.2376
|View full text |Cite
|
Sign up to set email alerts
|

Dung odours signal sex, age, territorial and oestrous state in white rhinos

Abstract: Mammals commonly communicate olfactorily via urine. However, the extent to which they communicate via dung, another waste product, is unknown. Behavioural studies suggest that mammals can obtain information from dung odours but are unclear about the information transmitted. Moreover, an understanding of the volatile organic compounds (VOCs) released from dung is limited. To address this, we analysed the odours emitted from the dung of free-ranging white rhinos, and found that 2,3-dimethylundecane signalled an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 52 publications
1
43
0
Order By: Relevance
“…White rhino (Ceratotherium simum) olfactory signals are concentrated in communal middens (also called dung piles or latrines) by individuals of all ages and sex (Owen-Smith 1973), where age, sex, territorial and oestrous state are identifiable via dung odours (Marneweck et al 2017a). These middens are located at strategic locations including territory boundaries, well-travelled rhino paths, and next to water sources (Owen-Smith 1973), which increases encounter probability.…”
Section: Introductionmentioning
confidence: 99%
“…White rhino (Ceratotherium simum) olfactory signals are concentrated in communal middens (also called dung piles or latrines) by individuals of all ages and sex (Owen-Smith 1973), where age, sex, territorial and oestrous state are identifiable via dung odours (Marneweck et al 2017a). These middens are located at strategic locations including territory boundaries, well-travelled rhino paths, and next to water sources (Owen-Smith 1973), which increases encounter probability.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying whether or not chemo‐sensory signals/cues differ between groups of interest is a major component of GC‐MS research . From simulation study 1, we found that when differences between groups were pronounced, and the structure of the underlying data was relatively simple, all methods resulted in comparable model performance.…”
Section: Classification Accuracy Is Related To Data Normalizationmentioning
confidence: 98%
“…Identifying whether or not chemo-sensory signals/cues differ between groups of interest is a major component of GC-MS research. [16,17,[19][20][21] From simulation study 1, we found that when differences between groups were pronounced, and the structure of the underlying data was relatively simple, all methods resulted in comparable model performance. When the data structure was more complex as in simulation study 2, calibrating against an external standard was the single most reliable normalization method for this purpose.…”
Section: Classification Accuracy Is Related To Data Normalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatouros, van Loon, Hordijk, Smid, & Dicke, 2005;Mattiacci et al, 2001;Pierre et al, 2011) and environmental monitoring (e.g. Rabaud, Ebeler, Ashbaugh, & Flocchini, 2002;Wu, Feng, Lo, Lin, & Lo, 2004) but not for animal body odour, particularly in vertebrates (but see Marneweck, Jürgens, & Shrader, 2017 for an application to dung odour). In contrast to rubbing a medium over the skin or fur or sampling secretions directly from scent glands, TD tubes do not necessarily require handling and capture of animals, as only the ambient air in the immediate vicinity of an animal is sampled.…”
Section: Introductionmentioning
confidence: 99%